Pengaruh Pemberian Reward dan Punishment Terhadap Kinerja Karyawan PT. Adam Kurnia Abadi - Adam, Andi Muchammad Naufal; Warganegara, Tri Lestira Putri (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
Economic development and competing companies that increasingly require companies to develop Human Resources who are members of a company or organization. The provision of rewards and punishments in accordance with the behavior shown at work is one of the company's management efforts to get the best performance from its employees. All employees of PT. Adam Kurnia Abadi with a total of 50 employees involved in the study as respondents. The researcher proposed three hypotheses in this study and analyzed using multiple linear regression with the help of the SPSS Version 24 Program. Rewarding has a significant influence on employee performance, while the punishment system does not have a significant influence on employee performance. However, the provision of rewards and punishment systems that are given at the same time can have a positive and meaningful influence on the performance of PT. Adam Kurnia Abadi. Therefore, the more appropriate the reward and punishment system that can be given by the management, the performance of PT. Adam Kurnia Abadi will increase. Keywords: Reward, Punishment, Kinerja Karyawan